Impact of anodal tDCS and virtual reality on cognitive dysfunction in patients with Multiple Sclerosis: Protocol of a double blind, randomized, prospective, controlled study - Lucilla Vestito; Cristina Schenone; Francesca Casazza; Roberto Modenesi; Angelo Iandolino; Maria Giuseppina Matichecchia; Lisbet Montes Saez; Massimiliano Botto; Marta Ponzano; Paola Gazzola; Erica Grange; Giampaolo Brichetto; et al. (PLoS ONE, 2025)
Background Cognitive impairment (CI) affects a significant proportion of people with Multiple Sclerosis (PwMS), even in the early stages of the disease, increasing fatigue perception and reducing quality of life. Various restorative interventions have been tested to mitigate CI, but their efficacy remains limited. Transcranial direct current stimulation (tDCS) has emerged as a promising add-on to conventional rehabilitation in several neurological conditions, including MS. Similarly, novel technologies such as exergames are gaining attention as supportive tools in the rehabilitation of PwMS. These approaches can be combined within integrated protocols to maximize therapeutic benefits on CI. However, robust evidence of efficacy is still lacking, and only one case report has been published to date. Aims The primary aim is to investigate the potential benefits of combining anodal tDCS (A-tDCS) with exergame-based training in the rehabilitation of CI in PwMS. The secondary aim is to assess whether the proposed protocol can provide sustained benefits over time. Methods 80 PwMS with CI will be consecutively enrolled and evaluated through a comprehensive neuropsychological battery. 40 participants will be randomized to the experimental group (EG) and 40 to the control group (CG). All participants will undergo 10 sessions of exergame-based rehabilitation. In addition, the EG will receive concurrent A-tDCS over the left dorsolateral prefrontal cortex, whereas the CG will receive sham stimulation. Assessments will be conducted at baseline, post-treatment, and at one and six months follow-up. Discussion We hypothesize cognitive improvements in both groups due to exergame training. However, we expect greater improvements in the EG compared with the CG. Furthermore, we hypothesize that the beneficial effects in the EG will be sustained over time. Clinical trials registration ClinicalTrials.gov, Identifier: NCT07114809 (Date: August 8th, 2025)